New Archaeological Studies in the Chicama Valley: The Chicama Archaeological Program Season 2021 - Tantaleán, Henry (2024)
This article aims to present the preliminary results of our research conducted in the Chicama valley situated in the department of La Libertad, Peru. During the 2021 season of the Chicama Archaeological Program, archaeological excavations were carried out in the archaeological sites Cerro Malabrigo, Licapa II, Pelenque 1 and Quebrada del Oso and systematic surveys in the area of Puerto Chicama, Cerro Malabrigo Sur and Huaca Pukuche. Within the framework of the study, a methodical registry was carried out in order to identify the social-temporal affiliation of the settlements. As a result, we have a broader and more diverse spectrum of the different types of settlements that occupied the Chicama valley throughout its pre-Hispanic occupation.